Free Tensor Fascia Lata Flap and Synthetic Mesh Reconstruction for Full-Thickness Chest Wall Defect - Jumpei Ono; Akira Takeda; Minekatsu Akimoto; Akira Iyoda; Yoshio Matsui; Yukitoshi Satoh; Eiju Uchinuma (Case Reports in Medicine)
A large full-thickness chest wall defect over 10 cm in diameter requires skeletal reconstruction and soft tissue coverage. Use of various flaps for soft tissue coverage was previously reported, but en bloc resection in each case affects these flap pedicles and sizes. We present a case of a 74-year-old man with a soft tissue tumor involving the left lateral chest wall. We performed an en block resection and skeletal reconstruction using a mesh, free tensor fascia lata (TFL) flap for soft tissue coverage. This procedure could be performed in one position. A fixed fascia lata of the flap was also useful for tight reconstruction with the mesh. We suggest that free TFL and/or anterior lateral thigh flap is a useful technique to reconstruct anterior to posterior lateral chest wall defects.